MENUMBUHKAN AKTIVITAS BELAJAR DAN HASIL BELAJAR MENGGUNAAN MODEL TGT MATERI BANGUN DATAR KELAS IV: Penelitian Kualitatif Deskriptif - Muhammad Luqman Hakim; Kartinah; Fenny Roshayanti; Retno Suci Handayani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to foster learning activities and learning outcomes of grade IV students of SDN Bendungan Kota Semarang towards the use of the Teams Games Tournament (TGT) learning model in learning mathematics flat building material. This research belongs to the type of descriptive qualitative research. The subjects taken in this study were students of class IVA SDN Damungan. Data collection techniques in the form of observations of student learning activity, student learning outcomes and questionnaires of student responses to learning using the Teams Games Tournament model. The results showed that the Teams Games Tournament model can increase students' understanding and learning activities in flat material mathematics lessons, besides that the Teams Games Tournament model is also very relevant to grow the learning outcomes of grade IVA students at SDN Bendungan Kota Semarang. From the responses of students, it was revealed that students are more interested in participating in learning using the TGT learning model because they can be more active, creative, and collaborate with their peers.